Mechanical Alloying of Fe-C System Based Alloy - Nurul Taufiqu Rochman (Indonesian Journal of Physics, 2008)
This paper reviews the research of the author’s group regarding mechanical alloying (MA) of Fe-C system based alloy over the last ten years. Powder mixtures of Fe-xC-yM (x and y=0~6 mass %, M: additive element such as Mn, Si, Cr) were mechanically alloyed (MAed) by using a planetary ball mill under Ar gas atmosphere for various time up to 100 h. The MAed powders then were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and differential thermal analysis (DTA). First, effect of MA time on powders particles was described. Effects of other MA conditions such as temperature, rotation speed and additive elements were then discussed in detail. In the Fe-C system based alloys, amorphization of graphite powders occur first during the early stage of MA and super-saturated iron solid solution is then formed and at the same time, the crystallite size becomes smaller. The carbon content reaches its limitation (about 1.30 at %). The condition of MA gave an effect to the alloying process.